The aesthetics of the grotesque in the novel El tungsteno by César Vallejo - Lopez-Saravia, Fernando J. (2021)
This article aims to demonstrate that in the novel El tungsteno by César Vallejo, the topic of violence can not only be analyzed at the content level, but also at the aesthetic level. With this objective, it was proposed to analyze the different fragments of the novel based on the hermeneutical methodology. The analysis based on the following variables: harrowing descriptions of the environment, animalization and the degradation of physiological needs based on the studies carried out by Kayser , Bajtin, Eco and Conelly. It was demonstrated that the author not only addresses the issue of violence in order to transmit a certain ideology (like most novels that belong to the regionalist tendency), but that the resources he uses allow to configure a universe where the aesthetic of the grotesque prevails with the aim of achieving a feeling of uncertainty and rejection in the reader.